6p^2 -5p -6 3/18/2014 | Paula from Woodland Hills, CA | 2 Answers | 0 Votes Mark favorite Subscribe Comment
Hi Paula, 6p²-5p-6 = 6p²-9p+4p-6 =3p(2p-3)+2(2p-3) =(3p+2)(2p-3) The solutions are 3p+2=0 p=-2/3 2p-3=0 p=3/2 3/18/2014 | Shelly J. Comment
by finding D = b^2-4*a*c , you can check whether the above equation is easily factorable. D=169, which is a perfect square, which means a factor able equation Using a quadratic equation, you can easily find out p = 18/12 or p=-8/12. Therefore, 6p^2-5p-6=(2p-3)(3p+2) 3/18/2014 | Chen Jang T. Comment Comments Show more of your solution process. How did you get p = 18/12 or p=-8/12? And how does that get to 6p^2-5p-6=(2p-3)(3p+2)? 3/18/2014 | Steve S. Comment
Show more of your solution process. How did you get p = 18/12 or p=-8/12? And how does that get to 6p^2-5p-6=(2p-3)(3p+2)? 3/18/2014 | Steve S.
Comments